Pengaruh Faktor Sosial Ekonomi Terhadap Loyalitas Konsumen Di Pasar Tradisional Ampel Kabupaten Boyolali - Eka Dwi Fitriani; Bayu Nuswantara (Universitas Sebelas Maret, 2018)
This study examines socioeconomic factors on consumer loyalty in choosing to shop at the traditional Ampel market in Boyolali Regency. In order for traditional markets to survive and develop in the competitive business world in competing for consumers, it must be able to understand it’s consumers. Many factors can influence consumer loyalty in choosing to shop in traditional markets. In this study the factors that are thought to influence are product prices, product quality, merchant service, product location and market days. The type of research used is a survey with 50 sampling using incidental sampling. The type of data used is primary data and secondary data. Data collection techniques using questionnaires and data analysis techniques used multiple linear regression. Instrument test results show all valid and reliable. Multiple linear regression test shows Y = -9,199 + 0.510 X1 + 0.460 X2 - 0.192 X3 + 0.708 X4 + 0.551 X5. It is shows that product price variables, product quality, market location and market day have a positive effect on consumer loyalty.